Fundamentals of materials science and engineering : an integrated approach. - Callister, William D., Jr., 1940- (Hoboken : Wiley, 2005)
This Second Edition of Fundamentals of Materials Science and Engineering continues to take an integrated approach to the topic organization. One specific structure, characteristic, or property type at a time is discussed for all three basic material types-metals, ceramics, and polymeric materials. This order of presentation allows for early introduction of non-metals and supports the engineer's role of choosing a material based on its characteristics.